Is Environmental Policy by Public Procurement Effective?. (July 2016) - Lundberg, Sofia; Marklund, Per-Olov; Strömbäck, Elon
Advocates of green public procurement (GPP) argue that the public sector can use its purchasing power to influence producers and consumers to reduce their negative impact on the environment. Our aim is to assess GPP as an environmental policy instrument and its ability to lead to the achievement of environmental objectives. Central to our analysis is the extent to which polluting firms choose to adapt to the public sector's environmental requirements and to invest in greener technologies. Our theoretical finding is that the potential of GPP to function as an objective effective instrument of environmental policy is limited and can actually be counterproductive. From an environmental policy point of view, it is crucial that the GPP aims for an environmental standard beyond the technology of the polluting firms and is designed with reference to defined environmental objectives.